PENGETAHUAN IBU MENGENAI MANFAAT ASI PADA BAYI - Umboh, Edelwina; Wilar, Rocky; Mantik, Max F. J. (e-Biomedik, 2013)
Abstract.Breast milk is the best food for the baby when he/she was born. Many researches prove that breast milk is the best and primary food for the baby because in the breast milk contain an antibody that the baby need to resist any kind of disease. The excellence of breast milk has been prove, however the tendency of the mother not to give an exclusive breast milk to their baby is bigger. It is influenced by some factors, such as occupation, age, and education.This studyisto know the relation between the knowledge of the mother about usefulness  of the breast milk for the baby with exclusive breast milk. Type of study is a descriptive cross sectional with field survey method.There are 80  mothers that be the research subject. The result is 12 mothers has a good knowledge, 39 mothers the knowledge is enough, and 29 mothers has a less knowledge. There are 41 mothers that give an exclusive breast milk and 39 mothers that don't, there is a meaningful relation with chi - square test (p=0.016).Conclusion: Where is the higher the knowledge of the mother about the usefulness of breast milk for the baby, the higher breastfeeding is success. Keyword: Exclusive breast milk, knowledge, mother.     Abstrak.Air susu ibu adalah makanan terbaik bagi bayi baru lahir.Banyak penelitian yang membuktikan bahwa Air Susu Ibu merupakan makanan terbaik dan utama bagi bayi karena di dalam ASI terkandung antibodi yang diperlukan bayi untuk melawan penyakit-penyakit yang menyerangnya.ASI sudah diketahui keunggulannya, namun kecenderungan para ibu untuk tidak menyusui bayinya secara eksklusif semakin besar. Hal ini dipengaruhi oleh berbagai macam faktor, antara lain pekerjaan, usia dan pendidikan. Tujuan penelitian ini untuk mengetahui hubungan antara pengetahuan ibu mengenai manfaat ASI pada bayi dengan pemberian ASI eksklusif. Jenis penelitian deskriptif potong lintang dengan metode survei lapangan.Terdapat 80 ibu yang menjadi subjek penelitian. Hasil yang di dapatkan 12 ibu memiliki pengetahuan baik, 39 ibu memiliki pengetahuan cukup, dan 29 ibu memiliki pengetahuan kurang. Yang memberikan ASI eksklusif sebanyak 41 ibu dan yang tidak sebanyak 39 ibu, terdapat hubungan bermakna dengan uji Chi-Square (p=0,016). Simpulan:Semakin tinggi pengetahuan ibu mengenai manfaat ASI pada bayi, semakin tinggi keberhasilan menyusui. Kata kunci. ASI eksklusif, ibu, pengetahuan